2019
DOI: 10.1111/sms.13572
|View full text |Cite
|
Sign up to set email alerts
|

Physical capacity, not skeletal maturity, distinguishes competitive levels in male Norwegian U14 soccer players

Abstract: Funding information IdrettsCampus BergenThe main aim of the present study was to compare skeletal maturity level and physical capacities between male Norwegian soccer players playing at elite, sub-elite and non-elite level. Secondary, we aimed to investigate the association between skeletal maturity level and physical capacities. One hundred and two U14 soccer players (12.8-14.5 years old) recruited from four local clubs, and a regional team were tested for bone age and physical capacities. Bone age was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The incremental test to exhaustion followed current recommendations for test duration [23], and was performed according to the standard protocol of the Norwegian Olympic Sports Centre (see e.g., [24]). Prior to the pre-test, subjects performed two familiarization tests to reduce the learning effect, following the recommendations of Edgett et al [25].…”
Section: Methodsmentioning
confidence: 99%
“…The incremental test to exhaustion followed current recommendations for test duration [23], and was performed according to the standard protocol of the Norwegian Olympic Sports Centre (see e.g., [24]). Prior to the pre-test, subjects performed two familiarization tests to reduce the learning effect, following the recommendations of Edgett et al [25].…”
Section: Methodsmentioning
confidence: 99%
“…Research on the physical performance characteristics of youth football players has made significant progress in recent years. Studies have revealed that elite youth football players are superior in anthropometrics (height, body mass, and body composition) ( Bidaurrazaga-Letona et al, 2016 ; Deprez et al, 2015a ; Nughes et al, 2020 ; Bongiovanni et al, 2020 ) and physical characteristics (speed, agility, anaerobic endurance, strength, and power) ( Emmonds et al, 2016 ; Aquino et al, 2017 ; Grendstad et al, 2020 ; Deprez et al, 2015b ), which are important factors influencing selection by coaches ( Patel et al, 2020 ; Bidaurrazaga-Letona et al, 2019 ; Nughes et al, 2020 ). As such, football players’ physical characteristics significantly influence the selection of elite vs non-elite players while they are still youths ( Itoh & Hirose, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study is part of a longitudinal research project, examining factors related to talent development in youth soccer [ 12 ]. The study design in the present study is descriptive, and match running performance data were collected during the 2018 season, from April to October.…”
Section: Methodsmentioning
confidence: 99%